Control interno de la cuenta inventarios y su incidencia en la rentabilidad de la empresa comercial Multipartes S.A. durante el período 2017 -2018 - Cortez Burgos, Vanessa Verónica (2019)
Every company requires an internal control system that provides a permanent control of inventories, so as to have updated the stocks both in quantity and in prices. The company Multipartes SA, is a family company established in 2002, which is dedicated to the marketing and sale of all types of automotive lubricants, whose economic activity has been decreasing due to the absence of an internal control of the account. inventories. The objective of the present investigation is to evaluate the internal control of the inventories account and its impact on the profitability of the commercial company Multipartes SA., During the period 2017 - 2018. As descriptive, explanatory and bibliographical research, the types of research were used. as methods used, the deductive, inductive and statistical method were applied, determining their respective population and sample. Within the results of the research as part of the specific objective one internal control questionnaires were applied to the different departments that make up the company on the system of registration and internal control of the inventories account. As part of the specific objective two indexes were applied. inventory rotation and finally as part of the specific objective three profitability indicators were applied. With the results obtained from the research, the conclusions and recommendations were finally prepared with their respective bibliography and annexes. Keywords: Internal control, inventories, profitability, inventory rotation indicators, profitability indicators